HoneyComb: An Application-Driven Online Adaptive Reconfigurable Hardware Architecture. (19th July 2012) - Thomas, Alexander; Rückauer, Michael; Becker, Jürgen
Abstract : Since the introduction of the first reconfigurable devices in 1985 the field of reconfigurable computing developed a broad variety of architectures from fine-grained to coarse-grained types. However, the main disadvantages of the reconfigurable approaches, the costs in area, and power consumption, are still present. This contribution presents a solution for application-driven adaptation of our reconfigurable architecture at register transfer level (RTL) to reduce the resource requirements and power consumption while keeping the flexibility and performance for a predefined set of applications. Furthermore, implemented runtime adaptive features like online routing and configuration sequencing will be presented and discussed. A presentation of the prototype chip of this architecture designed in 90 nm standard cell technology manufactured by TSMC will conclude this contribution.